Bone Regeneration in Vertical Osseous Defect in Periodontitis Patients using Bovine Colostrum - P. L. Ravishankar; Preethikaa Guruprasath; Padmaja Vangipuram; Jasmine Vaidya; G. Visithiriyan; A. Thirumal Raj; Shilpa Bhandi; Shankargouda Patil; Snehashish Ghosh (Case Reports in Dentistry)
Background. The treatment plan for periodontitis may include both nonsurgical and surgical phases. During surgical procedures, bone grafts and barrier membranes were used after degranulation in order to achieve healing. Colostrum is one of the materials that is composed of bioactive components which has either osteoinductive or regenerative potential. Aim. The aim of the present study is to evaluate the effectiveness of bovine colostrum as bone regeneration material in periodontitis. Case Description. Clinical periodontal parameters, including probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), and plaque index (PI), were evaluated. Patients who were diagnosed with localised periodontitis were selected. Three patients presenting vertical defect at buccal sites were treated with bovine colostrum. Following nonsurgical treatment, flap surgery was performed using bovine colostrum. After 6 months, favourable clinical and radiographical improvements were obtained. Conclusion. All cases showed reduction in PD; these findings suggest that the bovine colostrum could favour periodontal regeneration. The clinical significance is that bovine colostrum is cost effective and easily available and enhances bone regeneration. It can therefore be used as an alternative to bone grafts during periodontal surgery.